Anthropological impacts determine the soil fungal distribution of Mediterranean oak stands - Pablo Martín-Pinto; Ignacio Sanz-Benito; María Santos; Juan Andrés Oria-de-Rueda; József Geml (Ecological Indicators, 2021)
Quercus pyrenaica-dominated forests are very widely distributed in Mediterranean ecosystems. Traditional forest use, such as coppicing to obtain firewood or livestock grazing under silvopastoral systems, and the current social abandonment of the rural environment have given rise to forest structures of different ages and at different stages of development. Thus, on the one hand, there are large areas of Q. pyrenaica coppice systems that produce a large amount of biomass that have a very high risk of driving forest fires. On the other hand, dehesas, which have very low tree density and are composed of very old trees that are susceptible to different types of environmental stress and have serious regeneration problems and a weak phytosanitary status. In addition, previous studies have suggested that the production of economically valuable edible mushrooms is negatively impacted by silvicultural management. To determine the effects of land management on these ecosystems, we analyzed the soil fungal communities associated with coppice stands (i.e., high-density coppice), high forest stands (i.e., low-density coppice that received silvicultural management 15 years ago to reduce the risk of wildfire), and old stands (i.e., dehesas) to assess their potential ecological roles in their conservation and the diversity of edible mushrooms. We also analyzed the edaphic variables associated with these systems (carbon, pH and the carbon/nitrogen ratio) to understand the dynamics of these fungal communities. We observed two distinguishable communities: pathogen-, parasite-, and endophyte-dominated dehesas and saprotroph- and ectomycorrhizal (ECM)-dominated coppice stands, with a mixed composition in high forest stands. ECM fungi correlated with stand age and structure, showing higher richness levels in high forest stands, particularly ECM fungi with short hyphal exploration type. Finally, the influence of stand age and structure due to land management significantly affected the variety of some edible genera, such as Boletus, Tuber or Terfezia.